Three‐Dimensional Plasmonic Micro Projector for Light Manipulation. (4th December 2012) - Chang, Chia Min; Tseng, Ming Lun; Cheng, Bo Han; Chu, Cheng Hung; Ho, You Zhe; Huang, Hsin Wei; Lan, Yung‐Chiang; Huang, Ding‐Wei; Liu, Ai Qun; Tsai, Din Ping
<x xml:space="preserve">Abstract</x> Using the curved arrangement of Au nanobumps, the scattering of surface plasmon waves are transformed into spots at desired locations and altitudes in three‐dimensional space. The light can be modulated into desired light patterns. This work is very promising for compact plasmonic circuitry, projection, live‐cell imaging, optical sensing, and holography. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>